INFLUENCE OF THE BOARD OF DIRECTORS, AUDIT COMMITTEE, MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON FINANCIAL DISTRESS IN COMPANIES (Jurnal Ipteks Terapan, 2023)
INFLUENCE OF THE BOARD OF DIRECTORS, AUDIT COMMITTEE, MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON FINANCIAL DISTRESS IN COMPANIES